Validation of a Questionnaire to Identify Respiratory Tract Infections in Children With Sickle Cell Disease. Issue 5 (July 2021) - De, Aliva; Anekwe, Chika V.; Kattan, Meyer; Yao, Yujing; Jin, Zhezhen; Brittenham, Gary M.; Lee, Margaret T.
Abstract : Background: No validated questionnaires have been published that are specific for identifying respiratory infections in children with sickle cell disease (SCD). Methods: A questionnaire was developed that included 6 respiratory symptoms (difficulty breathing, wheezing, fever, cough, runny or stuffy nose, and sore throat) to identify respiratory events for a clinical trial. The questionnaire results were compared with identification of viral respiratory pathogens from nasal samples by reverse transcriptase polymerase chain reaction. Results: Eighty questionnaire responses (40 with symptom/s and 40 without) paired with isolation of viral respiratory pathogen from nasal samples were obtained from 53 children with SCD, ages 4 to 18 years over 2 separate periods in different seasons. The questionnaire yielded a sensitivity of 82%, specificity of 72% with an overall accuracy of 76%. The kappa value was 0.53, indicating moderate agreement, and the Fleiss' kappa test statistic was 4.77 with P <0.001, indicating that agreement between the 2 methods was not by chance. Conclusion: These results provide evidence for validity of this 6-symptom respiratory questionnaire in identification of respiratory viral infections for use in SCD-related research. Abstract : Supplemental Digital Content is available in the text.